(untitled) - Fairclough, Norman (London, 2003)
Drawing on a range of social theorists from Bourdieu to Habermas, as well as his own research, Norman Fairclough's book presents a form of language analysis with a consistently social perspective. His approach is illustrated by and investigated through a range of real texts, from written texts, to a TV debate about the monarchy and a radio broadcast about the Lockerbie bombing. The student-friendly book also offers accessible summaries, an appendix of example texts, and a glossary of terms and key theorists.
Keywords: Social sciences,Social sciences,Khoa học xã hội; Research,Methodology,Authorship